ANALISA TINGKAT PENGETAHUAN, PERSEPSI DAN SIKAP MASYARAKAT TERHADAP KEHALALAN OBAT DI RUMAH SAKIT ISLAM SULTAN AGUNG - Rizky, Inesya Febrianing; Agnes Febriyanti Pratiwi; Siti Komariyah (Journal of Innovation Research and Knowledge, 2024)
Medicine is one of the pharmaceutical products that plays an important role in health. In general, the definition of medicine is a substance used to diagnose, prevent, reduce, eliminate, cure disease or symptoms, injuries or physical and spiritual disorders in humans or animals, beautify the body or parts of the human body. Medicines that have a halal logo are very difficult for the public to obtain compared to other products such as food/drinks, this is because the number of medicines that are halal certified is still small compared to food/drinks. The aim of this research is to measure the level of knowledge, perceptions and attitudes of the community towards halal medicine at the Sultan Agung Islamic Hospital. This research is observational research, the sampling technique uses purposive sampling. The instrument used is a questionnaire. The variables observed were the level of knowledge, perceptions and attitudes of the community towards halal medicine. The population in this study were patients at the Sultan Agung Islamic Hospital, while the sample was the population that met the specified criteria. The inclusion criteria are, being >17 years old and willing to be a respondent. Exclusion criteria are respondents who do not fill out the questionnaire completely. Based on the research results, knowledge parameters get an average percentage of 85%, attitude parameters get an average percentage of 77% and perception parameters get an average percentage of 76%. From these data it can be concluded that the level of knowledge, attitudes and perceptions of the community at Sultan Agung Islamic Hospital regarding halal medicine are included in the good category.